The opioid receptor: emergence through millennia of pharmaceutical sciences - Fairbanks, Carolyn A.; Peterson, Cristina D. (Frontiers in Pain Research, 2023)
Throughout history humanity has searched for an optimal approach to the use of opioids that maximizes analgesia while minimizing side effects. This review reflects upon the conceptualization of the opioid receptor and the critical role that the pharmaceutical sciences played in its revelation. Opium-containing formulations have been delivered by various routes of administration for analgesia and other therapeutic indications for millennia. The concept of a distinct site of opium action evolved as practitioners developed innovative delivery methods, such as intravenous administration, to improve therapeutic outcomes. The introduction of morphine and synthetic opioids engendered the prevalent assumption of a common opioid receptor. Through consideration of structure-activity relationships, spatial geometry, and pharmacological differences of known ligands, the idea of multiple opioid receptors emerged. By accessing the high-affinity property of naloxone, the opioid receptor was identified in central and peripheral nervous system tissue. The endogenous opioid neuropeptides were subsequently discovered. Application of mu-, delta-, and kappa- opioid receptor-selective ligands facilitated the pharmacological characterization and distinctions between the three receptors, which were later cloned and sequenced. Opioid receptor signal transduction pathways were described and attributed to specific physiological outcomes. The crystal structures of mu, delta, kappa, and nociceptin/orphanin FQ receptors bound to receptor-selective ligands have been elucidated. Comparison of these structures reveal locations of ligand binding and engagement of signal transduction pathways. Expanding knowledge regarding the structure and actions of the opioid receptor fuels contemporary strategies for driving the activity of opioid receptors toward maximizing therapeutic and minimizing adverse outcomes.